2004
DOI: 10.1023/b:aibe.0000030244.92791.63
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with HIV/AIDS Knowledge and Risk Perception in Rural Malawi

Abstract: Measures of HIV/AIDS knowledge and risk perception are important because they are often linked to behavioral change both in theory and in practice. This study examines knowledge and risk perception by assessing their relationship with demographic characteristics, first source of HIV/AIDS information, and behavioral and cognitive risk exposures among men and women in a rural district of Malawi. The data come from a panel study of 940 women aged 15-34 years and 661 men aged 20-44 years. Descriptive statistics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 11 publications
9
56
1
1
Order By: Relevance
“…There is evidence that STI/HIV prevention campaigns have been successful in increasing public awareness about the epidemiologic predictors of STI/HIV (i.e., number of partners, previous STIs, condom use), but this has generally not translated into behavior change. [32][33][34] Moreover, few researchers have considered whether individuals use these predictors when evaluating their own STI/HIV risk. An exception is a study of adolescent women that found participants were aware of what defines high risk sexual behavior, but those engaging in the behaviors rated their chances of contracting an STI/HIV as low because they did not consider their partner a risk.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that STI/HIV prevention campaigns have been successful in increasing public awareness about the epidemiologic predictors of STI/HIV (i.e., number of partners, previous STIs, condom use), but this has generally not translated into behavior change. [32][33][34] Moreover, few researchers have considered whether individuals use these predictors when evaluating their own STI/HIV risk. An exception is a study of adolescent women that found participants were aware of what defines high risk sexual behavior, but those engaging in the behaviors rated their chances of contracting an STI/HIV as low because they did not consider their partner a risk.…”
Section: Discussionmentioning
confidence: 99%
“…Many adolescents are unaware of what constitutes risky sexual behaviour (Barden-O'Fallon, deGraft-Johnson, Bisika, Sulzbach, Benson & Tsui 2004;Macintyre, Rutenberg & Brown 2004;Pettifor, Rees, Steffenson, Hlongwa-Madikizela, MacPhail, Vermaak, et al 2004;Sarker, Milkowski, Slanger, Gondos, Sanou, Kouyate, et al 2005). Furthermore, most of the adolescents living with HIV do not know they are infected (UNAIDS 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Despite high HIV prevalence and high rates of sexual risk behaviors in South Africa and other Sub-Saharan African countries, young people in these countries often perceive themselves as being at low risk of HIV infection (Ajzen and Fishbein, 1980;Barden, 2004). One explanation for this is that youth may underestimate risks in general because of a feeling of invulnerability (Macintyre, 2004;Moore and Rosenthal, 1991).…”
Section: Youth Attitude Towards Hiv/aids and Stdi'smentioning
confidence: 99%